2010
DOI: 10.1007/s11605-010-1218-7
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis and Management of Wound Infections after Elective Colorectal Surgery: A Survey of the American Society of Colon and Rectal Surgeons Membership

Abstract: Based on the practices and beliefs in the surgical community, it is our hope that a multi-institutional study can be carried out to objectify best practices in both the effective and cost-effective management of this common condition and to reduce the wide variation in the treatment of surgical site infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 29 publications
0
21
1
Order By: Relevance
“…6,7 Although the current guidelines recommend the use of several antimicrobial agents, no specific regimen has been studied in ABX for Laparoscopic Colorectal Surgery case of the laparoscopic colorectal surgery. [9][10][11] In case of open colorectal surgery, only 36% of colorectal surgeons reported using oral-parenteral ABX in 2010 in comparison with 92% in 1990, 19,20 despite the recently proven efficacy of oral-parenteral prophylaxis in randomized trials and meta-analyses. [13][14][15] Our multicenter randomized controlled trial has shown that in patients undergoing elective laparoscopic colorectal surgery, the oral and IV ABX significantly reduces the incidence of SSIs compared to the IV prophylaxis alone (OR ¼ 0.536; 95% CI: 0.305-0.940; p ¼ 0.028).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Although the current guidelines recommend the use of several antimicrobial agents, no specific regimen has been studied in ABX for Laparoscopic Colorectal Surgery case of the laparoscopic colorectal surgery. [9][10][11] In case of open colorectal surgery, only 36% of colorectal surgeons reported using oral-parenteral ABX in 2010 in comparison with 92% in 1990, 19,20 despite the recently proven efficacy of oral-parenteral prophylaxis in randomized trials and meta-analyses. [13][14][15] Our multicenter randomized controlled trial has shown that in patients undergoing elective laparoscopic colorectal surgery, the oral and IV ABX significantly reduces the incidence of SSIs compared to the IV prophylaxis alone (OR ¼ 0.536; 95% CI: 0.305-0.940; p ¼ 0.028).…”
Section: Discussionmentioning
confidence: 99%
“…However, while there is evidence on specifically the benefits of the latter on SSI risk, some reports suggest a decrease in the use of oral antibiotics: 30 92% of surgeons reported using oral antibiotics in 1992 31 while this was only 36% in 2010. 32 Additionally, information from billing databases does not necessary reflect what is actually administered to the patient as there might be a mismatch between the two. Given the de-identified nature of the dataset auditing was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale of both strategies being used together is that oral non-absorbed antibiotics reduce the inoculum of bacteria contaminating the surgical site from the colon, and systemic antibiotics provide a safety net of effective drug in the soft tissues to minimize the risk of infection. Interestingly, the use of oral non-absorbable antibiotics among [30,31]. Popularized by Nichols and Condon, the ''standard'' oral antibiotic regimen in colorectal surgery utilizes nonabsorbable antibiotics given the day before surgery [7].…”
Section: Discussionmentioning
confidence: 99%